Context modeling and reasoning in a smart space environment - Yin, Erin Goh Yii; Tze, David Chieng Heng; Churn, Ngeow Yen; Kung, Low Hsien; Mustapha, Azhar (2007)
There has been an increase of focus in context modeling and reasoning research for ubiquitous network environment in recent years. In this paper, we present a novel approach to model and reason networked devices' context information through the support of a Context Modeling and Reasoning Engine (CMRE) architecture. As a proof of concept, a prototype system has been developed to demonstrate the functionalities of CMRE. To enhance the performance of CMRE, a Context Reasoner is embedded with a rule translator and a rule filter algorithm. With such a mechanism in place, various types of reasoning tasks can be performed with minimal conflicting contexts and rules in order to preserve the consistency of context knowledge database. Also, our CMRE prototype is further integrated with a Web-based Device Workflow Management (WDWM) engine, which enables end users to customize their workflow preferences in a user friendly manner.